UMP to have on-campus driverless bus developed by in-house researchers - T.N., Alagesh (New Straits Times Press (M) Bhd., 2022)
KUANTAN: Universiti Malaysia Pahang (UMP) students are set for a futuristic ride once the shuttle buses in the Pekan campus go driverless by the end of this year.